Harald Gustafsson: Political Interaction in the Old Regime. Central Power and Local Society in the Eighteenth-Century Nordic States. (Studentlitteratur, 1994). 195 s. - Mikkelsen, Jørgen (Historie/Jyske Samlinger, 1995)
-